2017
DOI: 10.1144/sp466.19
|View full text |Cite
|
Sign up to set email alerts
|

Climatological trends and anticipated karst spring quantity and quality: case study of the Slovene Istria

Abstract: The behaviour of aquifers with karst porosity is dependent on hydrological conditions. This is due to the peculiar characteristics of the groundwater flow and dynamics of hydrological processes in karst. As a result, karst aquifers are especially vulnerable to the effects of environmental change. We assessed the long-term climatological and hydrological trends and the short-term effects of increasingly frequent extreme hydrological events (droughts) for the Mediterranean karst spring Rižana in SW Slovenia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In addition to these human-driven impacts, studies from karst areas in China suggest that the discharge of springs can also be adversely affected by climate change (Hao et al, 2009;Jia et al, 2017). This is also supported by a study from Ravbar et al (2018), which concluded that climate change might severely affect water availability in the Mediterranean region.…”
Section: Conservation Status and Human Impactmentioning
confidence: 82%
“…In addition to these human-driven impacts, studies from karst areas in China suggest that the discharge of springs can also be adversely affected by climate change (Hao et al, 2009;Jia et al, 2017). This is also supported by a study from Ravbar et al (2018), which concluded that climate change might severely affect water availability in the Mediterranean region.…”
Section: Conservation Status and Human Impactmentioning
confidence: 82%